Since line segment JL is the perpendicular bisector of line segment KM, point H must be the midpoint of segment KM. Therefore, the lengths of segments KH and HM must be equal.
Given:
- \( KH = 6y + 3 \)
- \( HM = 2y + 7 \)
Since \( KH = HM \), we can set the two expressions equal to each other:
\[ 6y + 3 = 2y + 7 \]
Next, we will solve for \( y \). First, we subtract \( 2y \) from both sides:
\[ 6y - 2y + 3 = 7 \]
This simplifies to:
\[ 4y + 3 = 7 \]
Next, we subtract 3 from both sides:
\[ 4y = 4 \]
Now, divide both sides by 4:
\[ y = 1 \]
Now that we have the value of \( y \), we can find the length of segment \( HM \):
Substituting \( y = 1 \) into the expression for \( HM \):
\[ HM = 2y + 7 = 2(1) + 7 = 2 + 7 = 9 \]
Thus, the length of segment \( HM \) is:
\[ \boxed{9} \text{ units} \]